Integrated UPLC-MS and Network Pharmacology Approach to Explore the Active Components and the Potential Mechanism of Yiqi Huoxue Decoction for Treating Nephrotic Syndrome - Feng, Dan; Li, Xiang-Ri; Wang, Zhao-Yi; Gu, Nian-Nian; Zhang, Shuang-Xi; Li, Chao-Feng; Chen, Yang; Ma, Zhi-Qiang; Lin, Rui-Chao; Zhang, Hong-Gui; Zhao, Chongjun (Frontiers in Pharmacology, 2022)
Background: Yiqi Huoxue Decoction (YQHXD) is a traditional Chinese medicine that promotes blood circulation, removes blood stasis, facilitates diuresis, and alleviates edema. It is composed of 10 herbal medicines and has extensive application in treating nephrotic syndrome (NS). However, the active components and the potential mechanism of YQHXD for treating NS remain unclear. Methods: We set up a sensitive and rapid method based on Ultra-High Performance Liquid Chromatograph-Mass (UPLC-MS) to identify the compounds in YQHXD and constituents absorbed into the blood. Disease genes were collected through GeneCards, DisGeNET, and OMIM database. Genes of compounds absorbed into blood were predicted by the TCMSP database. We constructed Disease-Drug-Ingredient-Gene (DDIG) network using Cytoscape, established a Protein-protein interaction (PPI) network using String, Gene biological process (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis was performed using DAVID. Cellular experiments were performed to validate the results of network pharmacology. Result: A total of 233 compounds in YQHXD and 50 constituents absorbed into the blood of rats were identified. The 36 core targets in the PPI network were clustered in the phosphatidylinositol 3 kinase-RAC serine/threonine-protein kinase (PI3K-AKT) and nuclear factor kappa-B (NF-κB) signaling pathways. Luteolin, Wogonin, Formononetin, and Calycosin were top-ranking components as potentially active compounds. Conclusion: The results of our studies show that YQHXD is able to enhance renal function, alleviate podocyte injury and improve adriamycin nephrotic syndrome.